ELIZABETH BENNET’S PERSONALITY IN THE NOVEL PRIDE AND PREJUDICE (A STUDY OF PSYCHOLOGY OF LITERATURE) - Aprilia, Wiwin; Natsir, M.; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research is focused on the main character Elizabeth Bennet in the novel Pride and Prejudice by Jane Austen with the study psychology of literature. The researcher used a qualitative descriptive method to describe the structure of Elizabeth Bennet's personality in the novel Pride and Prejudice and the type of Elizabeth Bennet's personality in the novel Pride and Prejudice. This study used the theory psychoanalysis by Sigmund Freud and the personality types by Florence Littauer as a supporting theory in solving the problems. The data in this research were words, phrases, sentences obtained from the novel Pride and Prejudice. Data collection techniques used the technique of reading and take notes. The data analysis technique used qualitative analysis which consists of three activities, such as data reduction, data displayed and drawing a conclusion. The results of this study indicate that, there is the impetus of id, ego and superego in Elizabeth Bennet. The impetus of the id in Elizabeth was able to be fulfilled by the responses of the ego and the basis of considerations' superego. In addition, Elizabeth Bennet’s personality categorized into the choleric personality type because it is known that the characteristic of personality from Elizabeth Bennet is included in the characteristics of the choleric personality type.